Central stress processing, T-cell responsivity to stress hormones and disease severity in multiple sclerosis. Issue 2 (4th April 2022) - Brasanac, Jelena; Hetzer, Stefan; Asseyer, Susanna; Kuchling, Joseph; Bellmann-Strobl, Judith; Ritter, Kristin; Gamradt, Stefanie; Scheel, Michael; Haynes, John-Dylan; Brandt, Alexander U.; Paul, Friedemann; Gold, Stefan M.; et al.
Abstract: Epidemiological, clinical and neuroscientific studies support a link between psychobiological stress and multiple sclerosis. Neuroimaging suggests that blunted central stress processing goes along with higher multiple sclerosis severity, neuroendocrine studies suggest that blunted immune system sensitivity to stress hormones is linked to stronger neuroinflammation. Until now, however, no effort has been made to elucidate whether central stress processing and immune system sensitivity to stress hormones are related in a disease-specific fashion, and if so, whether this relation is clinically meaningful. Consequently, we conducted two functional MRI analyses based on a total of 39 persons with multiple sclerosis and 25 healthy persons. Motivated by findings of an altered interplay between neuroendocrine stress processing and T-cell glucocorticoid sensitivity in multiple sclerosis, we searched for neural networks whose stress task-evoked activity is differentially linked to peripheral T-cell glucocorticoid signalling in patients versus healthy persons as a potential indicator of disease-specific CNS–immune crosstalk. Subsequently, we tested whether this activity is simultaneously related to disease severity. We found that activity of a network comprising right anterior insula, right fusiform gyrus, left midcingulate and lingual gyrus was differentially coupled to T-cell glucocorticoid signalling across groups. This network's activity was simultaneously linked to patients' lesion volume, clinical disability and information-processing speed. Complementary analyses revealed that T-cell glucocorticoid signalling was not directly linked to disease severity. Our findings show that alterations in the coupling between central stress processing and T-cell stress hormone sensitivity are related to key severity measures of multiple sclerosis. Abstract : Brasanac et al . report that the link between stress-induced brain activity and stress hormone T-cell sensitivity in multiple sclerosis patients differed from that in controls. Simultaneously, this activity was linked to patients' disease severity. This might suggest that an altered CNS–immune system crosstalk in multiple sclerosis is clinically meaningful. Graphical Abstract: Graphical Abstract